2002
DOI: 10.1258/0956462021924785
|View full text |Cite
|
Sign up to set email alerts
|

HIV risk behaviour among gay and bisexual men in Budapest, Hungary

Abstract: HIV is a growing public health threat in Central and Eastern Europe. In Hungary and a number of other countries, men who have sex with men (MSM) account for a high proportion of HIV infections. However, there has been very little systematic study of the sexual risk practices and characteristics of MSM in this region. This study surveyed 469 MSM recruited in Budapest gay community venues in June 2001. Half the men (50%) engaged in unprotected anal intercourse (UAI) in the past 3 months. Of these, 40% of men's i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 1 publication
3
21
0
Order By: Relevance
“…This study found, as reported in several other Eastern European countries, that just about onethird of MSM reported having sexual contact with a female in the past 6 months (Amirkhanian et al, 2006;Amirkhanian et al, 2001;Csepe, Amirkhanian, Kelly, McAuliffe, & Mocsonoki, 2002). Higher percentages of bisexual activity by MSM have been reported in Albania and Croatia .…”
Section: Discussionsupporting
confidence: 81%
“…This study found, as reported in several other Eastern European countries, that just about onethird of MSM reported having sexual contact with a female in the past 6 months (Amirkhanian et al, 2006;Amirkhanian et al, 2001;Csepe, Amirkhanian, Kelly, McAuliffe, & Mocsonoki, 2002). Higher percentages of bisexual activity by MSM have been reported in Albania and Croatia .…”
Section: Discussionsupporting
confidence: 81%
“…Cross-national comparisons also point to similarities in characteristics of the samples used in our study and those carried out in St. Petersburg, Budapest, Bratislava, and Tirana (Family Health International, 2006;Csepe et al, 2002;Stanekova et al, 2000;Amirkhanian et al, 2001;Amirkhanian et al, 2006). All but one of these studies recruited a large number of above-average educated urban MSM (roughly 40% of respondents in St. Petersburg, Budapest, and Zagreb had a college education) whose median age ranged from 25 to 29 years.…”
Section: Discussionmentioning
confidence: 69%
“…Two of the studies, the St. Petersburg and the Budapest study, analyzed correlates of condom use at last anal sex (Amirkhanian et al, 2001;Csepe et al, 2002). Of the indicators that were included in our study, the St. Petersburg study found significant effects of steady relationship and HIV knowledge.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the Soviet era, homosexual behavior was criminal, and many MSM still remain hidden and receive little HIV/STD prevention. Recent studies have found high rates of unprotected sex, commercial sex, and bisexual behavior among MSM in Eastern Europe [10][11][12][13][14][15]. There is an urgent need to develop effective, culturally-pertinent HIV prevention intervention approaches for MSM in this region.…”
Section: Introductionmentioning
confidence: 99%